Viral News on Social Media. Issue 1 (2nd January 2019) - Al-Rawi, Ahmed
Abstract : Viral news is defined as networked news stories that spread online mostly through social media in a much faster and wider manner than other news stories, and this study investigates the elements that make news viral on two social media platforms. The goal is to fill a gap in the literature on viral news especially on social media news as previous communication studies mostly focused on news sharing habits on the news organizations' websites as well as editors' news selection criteria. The top 50 news stories are selected for this study by examining the most viewed videos on the Guardian, the New York Times, Washington Post and Wall Street Journal's YouTube channels as well as their most retweeted news stories. The study introduces a mixed model to examine viral news, borrowing from previous studies on emotions and others that focused on news worthiness. The results indicate that social media news readers prefer to read and share overwhelmingly positive news, while social significance and unexpectedness in news stories are the most appealing viral news elements.